Emicizumab Prophylaxis in Hemophilia A - Wohab, Md. Abdul; Banu Choudhury, Nilufar Akhter; Nusrat Ara, Umme (Journal of Neonatal Surgery, 2025)
Emicizumab is a monoclonal antibody that bridges activated factor IX (FIX) and factor X (FX) to replace the function of missing activated factor VIII (FVIII) in hemophilia A patients irrespective of FVIII inhibitor status. This study assessed the effectiveness of emicizumab in preventing bleeding episodes in children with hemophilia A. This prospective observational study included patients with moderate to severe hemophilia A who were undergoing episodic FVIII replacement therapy. The primary endpoint was the difference in annualized bleeding rates (ABR) and the secondary endpoint was the difference in Hemophilia Joint Health Score (HJHS) before and after emicizumab prophylaxis. A total of 17 male hemophilia patients were included, the mean age was 7.5 (SD: ±2.3) years, and most of them had moderate hemophilia A [63.3%]. Before prophylaxis, the median ABR was 18 (interquartile range [IQR]: 12–28), and 93.3% of patients had ABR greater than eight, whereas after prophylaxis the median ABR decreased significantly (median [IQR]: 0 [0.0–0.4], p < 0.001), and 56.7% had zero bleeds. ABR was not significantly different in patient with and without FVIII inhibitors. The HJHS scores significantly improved after prophylaxis (10 vs. 2.5, p < 0.001). The bleeding events were reduced significantly (17 vs. 0.0, p < 0.001), and zero new target joints were reported after prophylaxis. Most of the patients [93.3%] did not face any serious adverse events after prophylaxis. Emicizumab prophylaxis was associated with a significantly lower rate of bleeding events among participants with hemophilia A, regardless of inhibitor status